Presentation of the manuscript of The Ragged Trousered Philanthropists at Congress House, 1959 (1959)
1959 1945-1960 "Presentation of the manuscript of The Ragged Trousered Philanthropists at Congress House, 1959" [T0523.jpg], 1959